Differentiation between the Concurrence of Offences and the Unity of Offence with Multiple Passive Subject - Ștefănuț Radu (EIRP Proceedings, 2021)
In the content of the article, the author sets out the practical, concrete way in which, with the help of technical-legal reasoning of the inductive method - typical of criminology - reasoning that underlie both the qualification of criminal acts and the legal framework can be analyzed and argued, setting out the criteria for differentiating between unity and plurality of offences in cases of plurality of subjects or multiple passive subject. The aspects presented have a certain scientific value that must be considered both at the time of legislating criminalizations (of the legal qualification) and by the practitioner on the occasion of the investigation of such criminal acts. The novelty of the study is the need for the legislator to address the plurality of social values defended in the complex offence, fundamental values in relation to the plurality of actions / inactions within this type of criminalization.